Importancia de la determinación de microalbuminuria como ayuda de diagnóstico de nefropatías en pacientes diabéticos atendidos en la dirección distrital de salud n° 06 – d 01 chambo riobamba en el periodo marzo 2013 – agosto 2013 - Sinchiguano Calapaqui, Mario Christian (2013)
The present investigative work contains basic knowledge of the microalbuminuria technique, for the diagnosis of Nefropatía Diabetic in the patients assisted in the Direction Distrital of Health N° 06-D 01 Chambo Riobamba. This research consists of general and specific objetives that are related to the topic, it aims to determine values of microalbuminuria in diabetic patients to help diagnose of diabetic nefropatías, is justified by having a broad understanding of the cause and consequences that can occur at the time not to treat this disease